Assessment of Reality of Ballast Water Management in Syrian Ports - صقر علاء (Latakia University Journal -Engineering Sciences Series, 2022)
The process of ballast water management in Lattakia port was evaluated, by identifying the legal frameworks and procedures used and in force in the port to manage ballast water carried on board ships entering the port, and monitoring the ships that visited the port during the study period, in terms of the quality of the approved standard for ballast water management. On board, through ballast water management records, as well as the international certificate for ballast water management carried by ships in accordance with the requirements of the International Convention for the Management of Ballast Water and Sediments, then evaluating port procedures to ensure that these ships apply the standard that they are obligated to apply according to their certificates, and to identify the monitoring, follow-up and analysis mechanisms in The port, if any, and a comparison of these procedures followed with the requirements of the agreement to determine the extent of compatibility and the size of the gap in our ports in its ballast water management in accordance with international requirements. As results were reached confirming the absence of the necessary laws and decisions, the absence of any documented and approved procedures for ballast water management, the absence of monitoring, follow-up and analysis of the effects of this water on the marine ecosystem in our ports and marine waters, and the existence of a large gap between the reality of managing these waters, and the international requirements in force in accordance with the agreement. International for ballast water and sediment management.